2019
DOI: 10.3847/1538-3881/ab580a
|View full text |Cite
|
Sign up to set email alerts
|

The Most Probable 3D Orbit for Spectroscopic Binaries

Abstract: Binary stars are a very important source of astronomical information. Those short-period binaries observed by means of both spectroscopy and interferometry can provide, through their corresponding orbits, precise values regarding individual masses as well as orbital parallaxes. For this reason, it is fundamental to attempt to optically resolve double-lined spectroscopic binaries. In the present article, we used the elaboration of a specific algorithm in order to determine the necessary telescope aperture to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(37 citation statements)
references
References 21 publications
10
26
1
Order By: Relevance
“…If we scale our masses to the Gaia parallax instead of our orbital parallax, the individual component masses turn out to be 1.10 and 0.98 M respectively, quite close to those from the isochrones. However, the spectral type of the primary (G0IV to G5IV) implies a mass between 1.26 to 1.20 M (see Table 19 on Abushattal et al (2020)), closer to the masses derived from our orbital parallax. The photometry suggests that the primary is leaving the main-sequence; in our HR diagrams the isochrone that best fits both components is the PARSEC 9 Gyr (see Figure 5).…”
Section: Hr Diagramsupporting
confidence: 83%
See 4 more Smart Citations
“…If we scale our masses to the Gaia parallax instead of our orbital parallax, the individual component masses turn out to be 1.10 and 0.98 M respectively, quite close to those from the isochrones. However, the spectral type of the primary (G0IV to G5IV) implies a mass between 1.26 to 1.20 M (see Table 19 on Abushattal et al (2020)), closer to the masses derived from our orbital parallax. The photometry suggests that the primary is leaving the main-sequence; in our HR diagrams the isochrone that best fits both components is the PARSEC 9 Gyr (see Figure 5).…”
Section: Hr Diagramsupporting
confidence: 83%
“…Unfortunately, all our latest observations cover the same sector of the orbit (see Figure 7). As a final note, the F8V spectral type for the primary implies a mass of 1.23±0.05 M (Abushattal et al (2020), Table 18), within 1σ of our dynamical mass (with prior) as shown in Table 4. .…”
Section: Hr Diagramsupporting
confidence: 70%
See 3 more Smart Citations